MANAJEMEN SUPERVISI AKADEMIK DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI SDN DEWI SARTIKA CBM KOTA SUKABUMI - Suharyanto H Soro; Sri Handayani; Nana Mulyana; Rahmat Mulyana; Tantan Hadian (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the management of academic supervision in improving the teachers’ pedagogic competency at SDN Dewi Sartika CBM Sukabumi by using qualitative descriptive research methods. The research was conducted by analyzing the stages of planning, organizing, implementing, and assessment. The research begins with conducting interviews and observations. Planning indicators involved 1) identifying supervision plans, 2) formulating goals and output criteria for academic supervision, 3) arranging academic supervision schedules, and 4) reviewing academic supervision instruments. Organizing indicators involved 1) determining the implementation of supervision and 2)determining the teacher who will be supervised. Implementation indicators involved 1) reviewing the administration of learning devices, 2) reviewing the lesson plans, 3) carrying out supervision of the implementation of the learning process, and 4) implementing supervision of the assessment of learning outcomes. While the assessment indicators involved 1) observing supervised observation of learning outcomes assessment, 2) analyzing the results of observations of the implementation of learning, 3) analyzing academic supervision data, and 4) determining the follow-up to academic supervision. Management of academic supervision is considered to be very necessary to improve the teacher’spedagogic competency, especially teachers’ accompaniment in the teaching and learning activities in the implementation of the independent curriculum. Based on the results of interviews and observations, it is found an achievement of 74.38% with sufficient criteria for the teacher's pedagogic competency in designing the plans, implementing the teaching and learning processes, and learning evaluation and assessment.